Seasonal assessment of heavy metal contamination of groundwater in two major dumpsites in Sierra Leone. Issue 1 (31st December 2023) - Sankoh, Abdul Aziz; Amara, Joseph; Komba, Tamba; Laar, Cynthia; Sesay, Alusine; Derkyi, Nana Sarfo; Frazer-williams, Ronnie
Abstract: Consumption of water contaminated with heavy metals has serious health consequences and these include hypertension, kidney disease, cancer, anaemia, brain damage, etc. However, groundwater pollution with heavy metals may occur naturally or anthropogenically as a result of water-rock interaction, dumpsite leachate, agricultural activities, or sewage percolation. Therefore, the apportionment of the specific sources of heavy metals to groundwater is vital to prevent and control its pollution to groundwater. The present work assessed thirty-four (34) groundwater samples from the vicinity of the Granvillebrook and Kingtom dumpsites, Freetown, Sierra Leone. The objective of the research was achieved by integrating geospatial, indexical, and multivariate statistical methods. The results showed that heavy metals such as Cu, Cr, Fe, and Mn exceeded the permissible levels in the majority of the groundwaters. As and Pb were below the detection level of the instrument in all the groundwaters analyzed. Seasonal variations revealed that the concentration of heavy metals is relatively higher in the dry season due to the effect of dilution. The heavy metal evaluation index and degree of contamination analyses respectively showed that 16.7 and 41.6% of the groundwaters in the Granvillebrook dumpsite are highly polluted by heavy metals. All the groundwater samples in the Kingtom dumpsites except well KW17 are unaffected by heavy metals. The principal component analysis showed that fuel combustion, brake abrasion, and discharge of municipal and industrial waste from the dumpsites are some of the anthropogenic sources that impact groundwater pollution in the study areas. The findings of this research revealed the urgent need to develop strategies to control and mitigate the occurrences of heavy metals and thus serve as a base for future research in the study areas.